2020
DOI: 10.1088/1757-899x/803/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of virtual reality in reducing fear of public speaking: A systematic review

Abstract: Public speaking is no doubt one of the most feared mode of oral communication. Such anxiety is often treated through cognitive behavior therapy (CBT). An arising alternative to this treatment is virtual reality exposure therapy (VRET) where user confronts feared stimuli in a controlled 3D environment designed for such purpose. Sense of presence in this medium elicits similar feeling when standing in front of a real audience. Because of this, several studies were conducted to test its effect on individuals suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In the context of public speaking training, some studies have tested the use of VR technology to reduce anxiety in university students. In a systematic review, Daniels et al (2020) identified 14 studies conducted from 2009 to 2019 that used VR as a tool to diminish public speaking anxiety (PSA). From these 14 studies, 7 belonged to clinical settings (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010;Lister, 2016;Lindner et al, 2018;Yuen et al, 2019;Zacarin et al, 2019).…”
Section: E Ects Of Vr To Treat Public Speaking Anxietymentioning
confidence: 99%
“…In the context of public speaking training, some studies have tested the use of VR technology to reduce anxiety in university students. In a systematic review, Daniels et al (2020) identified 14 studies conducted from 2009 to 2019 that used VR as a tool to diminish public speaking anxiety (PSA). From these 14 studies, 7 belonged to clinical settings (Wallach et al, 2009(Wallach et al, , 2011Lister et al, 2010;Lister, 2016;Lindner et al, 2018;Yuen et al, 2019;Zacarin et al, 2019).…”
Section: E Ects Of Vr To Treat Public Speaking Anxietymentioning
confidence: 99%
“…This knowledge may be helpful in training public speakers as symptoms of PSA can be triggered by VR training and thus, enabling public speaking simulation. Furthermore, according to Wallach et al (2009) or Daniels et al (2020), VR can help reduce this anxiety too and thus we imply that virtual worlds are used to reduce PSA by using the stimuli identified in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Meta-analysis (Reeves et al, 2021a) and systematic literature reviews (Daniels et al, 2020) support these findings. Cognitive behavior therapy (CBT) and virtual reality exposure therapy (VRET) help treat PSA (Daniels et al, 2020). Daniels et al (2020) even highly recommended the use of VR to treat PSA and reported reduction of PSA levels ranging from 7.8 % up to 54.7 %.…”
Section: Literature Reviewmentioning
confidence: 85%
See 2 more Smart Citations